Kedudukan Hukum Harta Kekayaan Akibat Perceraian - I Nyoman Sumardiana; I Nyoman Putu Budiartha; Desak Gde Dwi Arini (Jurnal Analogi Hukum, 2020)
As long as a marriage is still going well and harmoniously, the legal consequences of marriage on property are still not felt, because they consider their property to be a unit to be used together in a common opinion and interest between husband and wife. Even if the husband between the husband and wife does a legal act against their property where the husband or wife actually has no right to do so, it means that there has been a violation of the law of marital property, but the legal consequences of the property in marriage are sometimes still not yet felt and not disputed by the husband and wife concerned. The formulation of the problem of this research is: how is the regulation of marriage assets in Indonesia and how the position of marital assets due to divorce is. The type of research used in this study is normative legal research. The results of the discussion in this study are: Regulation of marriage assets is pluralistic. Law No. 1 of 1974 concerning Marriage has regulated the problem of wealth, but the regulation in the law is very concise and incomplete, so that it cannot be used as a basis for resolving marital wealth disputes that occur between husband and wife when the marriage is broken, especially if caused by divorce. Therefore according to the provisions of Article 66 UUP, because it has not been regulated in full and in detail, then regarding the settlement of marriage assets using the law of each husband and wife concerned. The position of marital property according to UUP in principle is carried out separately in the sense that there is no unity as stipulated in the Civil Code. According to Article 35 UUP of marriage property consists of two types: a). Joint assets, namely assets acquired by a husband and wife during a marriage; and b). Default Assets are assets acquired and already owned by husband and wife before marriage.